Appreciation Workshop on Climate-Resilient Agriculture for the Local Government Officials of Quezon Province (4th District): A Workshop Report - Bayot, Ruvicyn S.; Vidallo, Rene R.; Palima, Carlo; Laco, Jonalyn; Jordan, Ruel; Locaba, Rico; Rosales, Belina O; Luistro, Aida; Anda, Girsky; Obligado, Maria Ella Cecilia (2019)
The two-day appreciation workshop on climate-resilient agriculture (CRA) was a collaborative activity among the Department of Agriculture Regional Field Office IVA (DA-RFO-IVA), the Municipal Government of Guinayangan Quezon, the International Institute of Rural Reconstruction (IIRR), and the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS). The workshop was designed for key local government officials – local chief executives, municipal agriculturists and municipal planning and development coordinators. The delivery involved presentations of concepts, activities, learning; field visits; and participatory action planning. This was an effort to bring the learning from the implementation of CRA-related interventions in the municipalities of Guinayangan and San Francisco to scale. This used the horizontal scaling approach to widen the spatial or geographic extent of the “product”. In this particular case, adaptation strategies were the ‘products’ that were promoted.